Impact of a pre-clinical skills course with Peer Assisted Learning (PAL) on preparedness and confidence levels of medical students in Africa - Cheryl Snyder; Rose Chisenga (Health for All Nations, 2017)
Background: Many benefits of pre-clinical medical skills training have been documented in technologically advanced nations, and in the past decade these courses have been introduced to developing countries. Curriculum that can prepare and build confidence in medical students must be cost effective, evidence-based, and culturally sensitive in places where there are severe resource limitations. In 2013, an initial pre-clinical skills course without assessments was introduced to medical students in Zambia. Later that year, a more developed course was launched to a second cohort integrating Peer Assisted Learning (PAL) and assessments. These trainers were prepared in advance with instructions in standardized skills, learning theory, effective feedback techniques, and use of rubrics to insure good inter-rater reliability in teaching and assessments. Methods: A quantitative study surveyed 108 students utilizing convenience sampling and a written questionnaire. Data collected compared preparedness and confidence in performing clinical skills of the intervention cohorts with the control group (medical students who preceded pre-clinical skills training). Results: Preparedness responses increased from 36.1% of the students in the control group to 90.9% in the intervention group who had been exposed to the PAL course with assessments (p value <0.001). Student confidence levels in history taking, physical exam skills, procedures, and the application of critical thinking skills diagnostically also showed improvement from 11.5-29.5% range in the control group to 77.3-86.4% range in the PAL cohort (p value <0.001). Conclusions: Exposure to pre-clinical training program especially utilizing PAL with assessments had a positive impact on the sense of preparedness and confidence levels for medical students beginning their clinical training years at the University of Zambia. Integration of PAL influenced academic development, clinical procedural standardization, appropriate curriculum additions, transitional support, and program sustainability. PAL may have beneficial application extending to basic science lab instruction in resource limited environments. Recommendation for future research would be integration of qualitative triangulation and reduction of variables in confidence data reporting.